Routing and switching essentials : Lab manual (Indianapolis, Indiana : Cisco Press, 2014)
The Routing and Switching Essentials Lab Manual provides students enrolled in a Cisco Networking Academy Routing and Switching Essentials course with a convenient, complete collection of all the course lab exercises that provide hands-on practice and challenges.
Chapter 1 -- Introduction to Switched Networks -- Chapter 2 -- Basic Switching Concepts and Configuration -- Chapter 3 -- VLANs -- Chapter 4 -- Routing Concepts -- Chapter 5 -- Inter-VLAN Routing -- Chapter 6 -- Static Routing -- Chapter 7 -- Routing Dynamical -- Chapter 8 -- Single-Area OSPF -- Chapter 9 -- Access Control Lists -- Chapter 10 -- DHCP -- Chapter 11 -- Network Address Translation for IPv4 --
Includes index.
Keywords: Routers (Computer networks) -- Handbooks, manuals, etc